Utilization of Silica Gel for the Synthesis of Geranyl Laurate and Citronellyl Laurate - Rosalina, Khoerunissa Novianti; Wukirsari, Tuti; Handayani, Sri; Hudiyono, Sumi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Geraniol and citronellol are monoterpenoid alcohols with diverse pharmacological activities. This research focuses on synthesized of geranyl laurate and citronellyl laurate using silica gel as an esterification catalyst. The FTIR peak spectra of silica gel showed that Si-OH, Si-O-Si group were observed. XRD showed that the silica gel is an amorphous phase. The reaction was conducted under reflux using a Dean–Stark trap. The reaction was monitored by TLC and then the product was purified using column chromatography. This work reported that silica gel can be utilized as a catalyst for preparing geranyl laurate and citronellyl laurate which proven by the spectra of FTIR, 1H-NMR, and 13C-NMR of the geranyl laurate and citronellyl laurate formed. The IR spectra of geranyl laurate and citronellyl laurate showed the presence of a carbonyl group (C=O) at 1744-1745 cm-1 and C-O from ester at 1170-1176 cm-1. The peak number and its chemical shift on 1H-NMR and 13C-NMR spectra further verified the structure of geranyl laurate and citronelyl laurate. In conclusion, silica gel can be utilized as a catalyst for preparing geranyl laurat and citronellyl laurate. Therefore a silica gel-based catalyst is promising to be developed for esterification applications.